2015
DOI: 10.1007/s12070-015-0885-9
|View full text |Cite
|
Sign up to set email alerts
|

Lobular Capillary Hemangioma of the Ethmoid Sinus: A Report of Two Cases

Abstract: Soft-tissue tumors are rare in the paranasal region. Lobular capillary hemangioma (LCH) is a distinctive vascular lesion most commonly seen on the skin and oral mucosa in the fourth and fifth decades of life. Forasmuch as the nasal cavity and paranasal sinuses are rare locations for LCH, it is not well known by many ENT surgeons. Here we present two cases of LCH of the ethmoid sinus. These cases are being reported owing to their scarcity as per the literature published global.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another particular aspect of a lesion limited to the sinus cavity is the possibility of developing bony erosion through mass effect and locoregional extension without invasion into the surrounding structures. In advanced cases with orbital implication, ocular symptoms (proptosis, reduced eye mobility, impaired vision, ocular globe displacement) will accompany the nasal ones [ 19 ]. When intracranial involvement is also present, the neurologic symptoms are associated with the nasal manifestations [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another particular aspect of a lesion limited to the sinus cavity is the possibility of developing bony erosion through mass effect and locoregional extension without invasion into the surrounding structures. In advanced cases with orbital implication, ocular symptoms (proptosis, reduced eye mobility, impaired vision, ocular globe displacement) will accompany the nasal ones [ 19 ]. When intracranial involvement is also present, the neurologic symptoms are associated with the nasal manifestations [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the tumor and the base of the skull and orbit should be thoroughly checked. Binesh et al reported two cases of ethmoid capillary hemangioma associated with bone erosion of the lamina papyracea in both adults and children; one case presented extensive bone erosion into the nasal septum and cribriform plate with extension into the anterior cranial fossa [ 19 ]. Pas M. et al presented a case of left ethmoid and sphenoid sinus capillary hemangioma with involvement of the left cavernous sinus, extensive bone erosion, and intrasellar and parasellar extension [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations